Estresse e recuperação em atletas de futsal e sua relação com biomarcadores sanguíneos - Araujo, Aureliano Carlos de (2013)
Physical exercise can be considered a stressor and the responses to this undergo changes with age, fitness levels, intensity of workload and somatotype. Within a season of training and competition, the futsal players are subjected to various physiological adaptations in response to the applied overload. Although it is a sport next to football, futsal has its specificities, regarding the anthropometric aspects, the physical, biochemical and hormonal responses. Accordingly, the aim of this study was to evaluate the physical, biochemical markers of muscle damage, serum hormone levels and stress and recovery in elite futsal in the preparation of basic training. Also investigate possible relationships between the study variables. The sample consisted of 12 athletes 25.8 ± 6.3 years. The variables studied were anthropometry, testosterone (T), cortisol (C), and creatine kinase (CK), anaerobic (peak power PP) and aerobic capacity, testosterone/cortisol ratio (TCR) and stress levels and recovery - RESTQ-Sports. Athletes surveyed had average BMI in the order of 24.5 ± 2.3, PP (W) 615.5 ± 190.2. With serum lactate levels around 8.4 mmol.L-1 ± 1.8 reached the critical velocity (VC) 181.6 m.min-1 ± 16.9, compared to the hormones present values for T 16.5 nmol.L-1 (± 6.2), and C 94.0 nmol.L-1 ± 41.4, as the marker of tissue injury CK 4.1 μKat.L-1 ± 1.7, scores total stress and total recovery had values of 2.2 ± 0.45 and 2.43 ± 0.38 respectively. The results showed that among the investigated athletes showed up important differences in behavior catabolic regarding the hormone cortisol, the testosterone/cortisol ratio. The behavior of the biomarker CK also drew attention, denoting stress levels with muscle recovery strategies inadequate for the period of training (basic training). With respect to motor performance, both teams were similar to those from other studies.